1996
DOI: 10.1172/jci118835
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit sucrase-isomaltase contains a functional intestinal receptor for Clostridium difficile toxin A.

Abstract: The intestinal effects of Clostridium difficile toxin A are initiated by toxin binding to luminal enterocyte receptors. We reported previously that the rabbit ileal brush border (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 56 publications
1
84
0
2
Order By: Relevance
“…difficile toxin A, like other ADP-ribosylating toxins, must bind to intestinal epithelial cells in vivo to exert its adjuvant activity. It is possible that the differences in the immune responses elicited by CT, EtxB, and TxA C314 are due, at least in part, to different properties for binding to the gastrointestinal and nasopharyngeal mucosa (39,46). Indeed, the sugar binding properties can confine lectins to specific cell populations, such as M cells in the Peyer's patches or the follicle-associated epithelium in nasopharyngeal tissue (5,24).…”
Section: Discussionmentioning
confidence: 99%
“…difficile toxin A, like other ADP-ribosylating toxins, must bind to intestinal epithelial cells in vivo to exert its adjuvant activity. It is possible that the differences in the immune responses elicited by CT, EtxB, and TxA C314 are due, at least in part, to different properties for binding to the gastrointestinal and nasopharyngeal mucosa (39,46). Indeed, the sugar binding properties can confine lectins to specific cell populations, such as M cells in the Peyer's patches or the follicle-associated epithelium in nasopharyngeal tissue (5,24).…”
Section: Discussionmentioning
confidence: 99%
“…Toxin A binds to a G protein-coupled receptor (11) on the luminal aspect of the apical intestinal epithelial cell membrane (12) and is then internalized where it activates MAPKs 1 (13), intracellular calcium release (14,15), release of reactive oxygen species (ROS) (12,16), and secretion of pro-inflammatory mediators (16,17). We previously reported that toxin A releases prostaglandin E 2 (PGE 2 ) into the ileal lumen of intact rats (5) and Alcantara et al (18) reported that toxin A-induced water and electrolyte secretion in vivo was significantly blocked by a COX-2 inhibitor.…”
mentioning
confidence: 99%
“…It has been suggested that these toxins are constructed of three functional parts (18). The C terminus, which consists of a large region of repetitive oligopeptides, is assumed to be important for receptor binding to the eukaryotic target (19). A hydrophobic region almost in the middle of the toxins is believed to participate in membrane translocation, and finally, the N terminus harbors the enzyme activity.…”
mentioning
confidence: 99%